Start question 26 by letting the three roots be
![](https://latex.codecogs.com/png.latex?\bg_white \alpha,\ \alpha, \text{ and } \beta \text{ where } \beta \neq \alpha)
.
Root theory (sum of roots, product of roots, etc) can then be used to get
![](https://latex.codecogs.com/png.latex?\bg_white a = \alpha)
for part (a) and then use the three equations to eliminate
![](https://latex.codecogs.com/png.latex?\bg_white \alpha)
and
![](https://latex.codecogs.com/png.latex?\bg_white \beta)
to get the relationship between the coefficients.
Alternatively, from the factor and multiple root theorems, you know that
![](https://latex.codecogs.com/png.latex?\bg_white P(\alpha) = P'(\alpha) = 0)
, which is another approach to part (a). Finding
![](https://latex.codecogs.com/png.latex?\bg_white \beta)
and substituting
![](https://latex.codecogs.com/png.latex?\bg_white P(\beta) = 0)
can then yield the relationships between coefficients.
Using root theory:
![](https://latex.codecogs.com/png.latex?\bg_white \begin{align*} \text{Sum of roots:} \qquad \alpha + \alpha + \beta &= -\frac{3p}{1} \qquad \implies \qquad \beta = -3p - 2\alpha \qquad \qquad \text{. . . (1)} \\ \text{Sum of roots in pairs:} \qquad \alpha \times \alpha + \alpha \times \beta + \beta \times \alpha &= \frac{3q}{1} \qquad \implies \qquad \alpha^2 + 2\alpha\beta = 3q \qquad \qquad \text{. . . (2)} \\ \text{Product of roots:} \qquad \alpha \times \alpha \times \beta &= -\frac{r}{1} \qquad \implies \qquad \alpha^2 = -\frac{r}{\beta} \qquad \qquad \text{. . . (3)} \\ \\ \text{Put (1) into (2):} \qquad \alpha^2 + 2\alpha(-3p - 2\alpha) &= 3q \\ \alpha^2 + 2p\alpha &= -q \\ (\alpha + p)^2 &= p^2 - q \\ \alpha &= -p \pm \sqrt{p^2 - q} \end{align*})
The same equation results from the multiple root theorem:
![](https://latex.codecogs.com/png.latex?\bg_white \begin{align*} P(x) &=x^3 + 3px^2 + 3qx + r \\ P'(x) &= 3x^2 + 6px + 3q \\ \text{Noting that $P'(\alpha) = 0$:} \qquad \qquad 0 &= 3\left(\alpha^2 + 2p\alpha + q\right) \\ \alpha^2 + 2p\alpha + p^2 &= -q + p^2 \\ \left(\alpha + p\right)^2 &= p^2 - q \end{align*})
You could put each possible solution into
![](https://latex.codecogs.com/png.latex?\bg_white P(x))
to establish which is the double root.
The coefficient result will arise from putting
![](https://latex.codecogs.com/png.latex?\bg_white \alpha)
and
![](https://latex.codecogs.com/png.latex?\bg_white \beta)
into one of the root theory equations and rearranging.